ETHNIC ENTREPRENEURSHIP AS A SOCIAL LIFT OF KOREANS IN JAPAN (REVIEW OF LITERATURE) - Н., Ем (Journal of Oriental Studies, 2019)
Ethnic entrepreneurship of Koreans outside the Korean peninsula is known almost on all continents of the world. In this paper, ethnic entrepreneurship is seen as “a specific way of organizing and con ducting business for ethnic minorities in a heterogeneous environment, based on the ethnic solidarity of the Korean community” in Japan. Despite the peculiarities of historical, political, socioeconomic and cultural conditions, and also in accordance with the theory of “shortcomings” in ethnic entrepreneur ship, Koreans in Japan demonstrate the possibilities of ethnic business as a social elevator. Based on the data of academic research, the author made an attempt to reveal the main directions of studying ethnic entrepreneurship as an instrument of social mobility. The author has revealed that the most characteristic for research on the Koreans in Japan are factors of socioeconomic growth as a result of entrepreneurial activity. For the research on Japan has not yet been studied is the internationalization of immigrant en trepreneurship. Key words: Koreans, Japan, ethnic entrepreneurship, social mobility.